CINE-DEMOGRAPHIES: POPULATION CRISIS IN LATE TWENTIETH CENTURY FILM CULTURE - Sully, Justin A. (My University, 2011)
This dissertation investigates the significance of demographic discourses and epistemologies over the last three decades of the Twentieth Century through the emergence of global film culture. Adopting a materialist reading of Serge Daney’s notion of a critical cine-demography, it explores three ways in which moments of population crisis over this period can be interpreted through film.
An experiment in method as much as an alternative periodizing account of late capitalist culture, the core chapters trace the evolution of a demographic imaginary through three, chronologically organized, case studies in the articulation of population crisis since the early 1970s: (1) the fear of overpopulation that reaches a frenzied pitch in the United States during the late 1960s and early 1970s; (2) anxiety about absolute population decline, situated in the context of Eastern Europe in the late 1990s; and (3) the emerging problem of population aging at the close of the century, centered in Western Europe, Japan and North America. In each of these cases, the dissertation identifies a corresponding archive of films that are marked at the level of their formal and narrative construction by the pressure of these demographic and discursive formations.
Keywords: Cinema; Culture; Crisis; Decline; Demography; Film and Media Studies; Film and Media Studies